Novel sources of edible films and coatings - Lopez, Olivia Valeria (2010)
Purpose of the review: This work reviews novel sources of edible films, coatings and formulations, including combined materials and a lipid phase, and highlights the main results of the most recent investigations carried out on the topic. New tendencies based on the incorporation of diverse active compounds (antimicrobials, antioxidants, nutraceuticals), that are applied on fruits and vegetables, are also mentioned. Findings: The diverse biological materials used in edible packaging formulations are generally classified as polysaccharides, proteins, lipids or resins. A plasticiser is often added to increase flexibility. Edible composite packaging materials have been developed by blending biocomponents for specific applications, taking advantage of complementary functional properties. They can be considered as new materials for formulating films and edible coatings. When composite films combine lipid compounds with a hydrocolloid-based structural matrix, the lipid components in the formulation reduce water transmission, whereas the hydrocolloid components serve as selective gas barriers and provide strength and structural integrity. Other additives can be added to modify and enhance film physical properties or functionality. Directions for future research: The potential of edible coatings has been recognised as an alternative or synergistic addition to conventional packaging to enhance food quality and protection. One important advantage of using edible films and coatings is that several active ingredients can be incorporated into the matrix and consumed with the food, improving safety or nutritional and sensory attributes. The new tendencies are to use edible coatings as carriers of functional ingredients by incorporating antimicrobial, antibrowning, and nutraceutical agents to improve the quality of fruits and vegetables. The development of new technologies to improve the delivery properties of edible films and coatings is one of the issues requiring future research. Most of the studies on food applications have been conducted at a laboratory scale. Further research on cost reduction and production in larger scales, and on stability and safety are necessary for promoting the feasibility of commercialised edible coated fruits and vegetables.